Vanadium, nickel and sulfur in crude oils and source rocks and their relationship with biomarkers: Implications for the origin of crude oils in Venezuelan basins. (February 2017) - López, Liliana; Lo Mónaco, Salvador
Graphical abstract: Highlights: V/Ni ratio is used to identify five crude oils groups. The five oil groups are also distinguished based on saturate biomarkers parameters. V/Ni groups crude oils regardless of their biodegradation level. Palaeoenvironment conditions determined by V/Ni agree with biomarkers parameters. Abstract: This work presents a study of vanadium, nickel and sulfur concentrations and biomarkers in a suite of crude oils and source rocks from three Venezuelan basins (Maracaibo and Eastern basins and Barinas sub-basin). Crude oils range from unaltered to altered by biodegradation, and source rocks are characterized by having different kerogen types (Type II, III or IV) and maturity levels (early mature to post-mature). Vanadium, nickel and sulfur concentrations, V/Ni or V/(V + Ni) and saturate biomarkers were used to classify the oils and source rocks based on inferred paleo-redox environment, lithology and maturity of the source rock. Oils are classified into five groups based on V/Ni ratios; they appear to be related to variations in the paleo-redox environment (from suboxic-dysoxic to anoxic-suboxic) of source rocks with variable lithological composition and organic matter input, regardless of their maturity or biodegradation level. These five groups are also classified based on biomarkers related to maturity, organic matter type, paleo-redox environment and source rock lithology. In source rocks, vanadium, nickel and sulfur concentrations, together with V/Ni or V/(V + Ni) ratios, provide information about the paleo-redox environment and are related to lithology, regardless of their maturity. These results also indicate variable paleo-redox conditions during the sedimentation of Venezuelan source rocks. All this suggests that, while the main source rocks in Venezuelan basins are well established, there are still uncertainties regarding their lateral and vertical variations in organic and inorganic facies and paleo-redox conditions. The presence of other source rocks contributing to the accumulation of hydrocarbons in the Venezuela basins is also a possibility.